'India Rising' and the Mixed Blessings of Globalisation. (December 2014) - Sharma, Shalendra D.
India has been a major beneficiary of economic globalisation. Yet, integration into the global economy has also made India vulnerable to the unpredictable swings in market sentiment. Nevertheless, the ultimate effects of cross-border economic forces also depend on the robustness of domestic policies. Potential vulnerabilities such as disruption in trade or financial flows can be mitigated by sound macroeconomic policies. Although 'licence raj' and 'export pessimism' is now a thing of the past, India's quasi-protectionist policies, coupled with the failure to deepen its integration into the global economy, have made the economy increasingly vulnerable to external forces—as seen when the United States Federal Reserve announced its decision to unwind its stimulus programme in mid-2013, resulting in deep sell-offs in emerging economies, especially India's currency, bond and equity markets.